The First Labour Hospital - Industrial Orthopaedic Society (Harlesden : Leveridge & Co.)
1923 1920s 4 pages appointment so that you can visit the hospital and talk the matter over on the spot, we are prepared to meet you in every way. You believe in the Brotherhood of Man . . . then put it into practice. You believe in Comradeship . . . then show the spirit of a Comrade. You believe in Co-operation . . . then co-operate in support of this human salvage plant. Just meditate over the following points, and whilst doing so try to remember your own importance as an individual, we cannot afford to lose the help of any single man in the work we are doing. 1. That the First Labour Hospital has rendered and is continuing to render an immense service to the workers. 2. That the treatment is of a character of especial benefit to industrial workers. 3. That the measure of freedom allowed the patients permits them to enter very largely into the social side of their life. 4. That every effort is made to make the patients feel as much at home as possible. 5. That all this is accomplished by the co-ordinated efforts of the members with their contribution of 1d. per week— and their good will. If you are interested you will want to know more about it, all enquiries should be addressed to— The Secretary, Manor House Hospital, Golders Green, N.W. 11. Leveridge and Co., Harlesden 36/H24/16